2020
DOI: 10.3389/fmicb.2020.01248
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Based Protein Profiling Reveals That Cephalosporins Selectively Active on Non-replicating Mycobacterium tuberculosis Bind Multiple Protein Families and Spare Peptidoglycan Transpeptidases

Abstract: As β-lactams are reconsidered for the treatment of tuberculosis (TB), their targets are assumed to be peptidoglycan transpeptidases, as verified by adduct formation and kinetic inhibition of Mycobacterium tuberculosis (Mtb) transpeptidases by carbapenems active against replicating Mtb. Here, we investigated the targets of recently described cephalosporins that are selectively active against non-replicating (NR) Mtb. NR-active cephalosporins failed to inhibit recombinant Mtb transpeptidases. Accordingly, we use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 80 publications
1
14
1
Order By: Relevance
“…We show that Mtb ΔclpB cells are sensitive to oxidants, especially diamide, while ΔhtpG cells are not. While htpG, like clpB, is not essential in Mtb (Lopez Quezada et al, 2020;Vaubourgeix et al, 2015), we find that cells lacking both nonessential chaperones are hypersensitive to host-like stresses that induce a nonreplicating state. Finally, a small molecule probe that targets HtpG mimics the effect of htpG disruption in ClpB-deficient Mtb.…”
mentioning
confidence: 62%
See 3 more Smart Citations
“…We show that Mtb ΔclpB cells are sensitive to oxidants, especially diamide, while ΔhtpG cells are not. While htpG, like clpB, is not essential in Mtb (Lopez Quezada et al, 2020;Vaubourgeix et al, 2015), we find that cells lacking both nonessential chaperones are hypersensitive to host-like stresses that induce a nonreplicating state. Finally, a small molecule probe that targets HtpG mimics the effect of htpG disruption in ClpB-deficient Mtb.…”
mentioning
confidence: 62%
“…While GA treatment demonstrated off-target effects in cells treated under nonreplicating conditions, a wealth of available GA analogs can be tested for cellular HtpG selectivity (Hadden et al, 2006;Ueda et al, 2019). We recently reported that Mtb ΔhtpG shows fourfold more cidality than wild type in the presence of select cephalosporins under nonreplicating conditions (Lopez Quezada et al, 2020). Perhaps this family of beta-lactams will synergize with GA analogs to kill Mtb.…”
Section: A Combination Of Modeling and Experimental Work Has Suggestedmentioning
confidence: 99%
See 2 more Smart Citations
“…These combinations differ both between and within bacterial species following the acquisition of the so-called "low-affinity" PBPs responsible for β-lactam resistance. In addition, the complexity of these combinations includes evolutionary unrelated enzymes, [5,[41][42][43] including unidentified ones, [44] in particular in M. tuberculosis. [42,45] This context prompted us to develop here a new strategy for affinity purification of β-lactam targets.…”
Section: Discussionmentioning
confidence: 99%